Research Progress on Main Symptoms of Novel Coronavirus Pneumonia Improved by Traditional Chinese Medicine - Luo, Chuan-hong; Ma, Le-le; Liu, Hui-min; Liao, Wei; Xu, Run-chun; Ci, Zhi-min; Lin, Jun-zhi; Han, Li; Zhang, Ding-kun (Frontiers in Pharmacology, 2020)
Novel coronavirus (COVID-19) pneumonia has become a major threat to worldwide public health, having rapidly spread to more than 180 countries and infecting over 1.6 billion people. Fever, cough, and fatigue are the most common initial symptoms of COVID-19, while some patients experience diarrhea rather than fever in the early stage. Many herbal medicine and Chinese patent medicine can significantly improve these symptoms, cure the patients experiencing a mild 22form of the illness, reduce the rate of transition from mild to severe disease, and reduce mortality. Therefore, this paper summarizes the physiopathological mechanisms of fever, cough, fatigue and diarrhea, and introduces Chinese herbal medicines (Ephedrae Herba, Gypsum Fibrosum, Glycyrrhizae Radix et Rhizoma, Asteris Radix et Rhizoma, Ginseng Radix et Rhizoma, Codonopsis Radix, Atractylodis Rhizoma, etc.) and Chinese patent medicines (Shuang-huang-lian, Ma-xing-gan-shi-tang, etc.) with their corresponding therapeutic effects. Emphasis was placed on their material basis, mechanism of action, and clinical research. Most of these medicines possess the pharmacological activities of anti-inflammatory, antioxidant, antiviral, and immunity-enhancement, and may be promising medicines for the treatment or adjuvant treatment of COVID-19 patients.